UPAYA MENUMBUHKAN MOTIVASI KERJA GURU DAN TENAGA KEPENDIDIKAN DALAM OPTIMALISASI MANAJEMEN KETENAGAAN - Ismail, Agung Deddiliawan; Jamil, Anis Farida (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2019)
Teacher competency improvement can be realized through increased work motivation. Motivation of teacher work is an encouragement that is possessed by a teacher to always work hard and face all problems in the hope of achieving the best results. Muhammadiyah 2 Batu Middle School has problems in increasing the work motivation of teachers and education staff. The service activities carried out aim as an effort to foster the motivation of work of teachers and education staff in optimizing staff management. The method implemented in this activity is the procurement of seminars. There are three techniques used in the delivery of material, namely 1) lecture, 2) question and answer, and 3) giving a questionnaire. The results of the material delivery activities aim to change the views of teachers and education personnel regarding their duties and obligations in accordance with the government regulation number 19 of 2017. In the question and answer activities active participants ask regarding the consistency of work motivation and the implementation of good learning. The questionnaire which aims to evaluate itself, produces 94% of teachers and education staff have work motivation and motivation to advance the school.